Associations of maternal prepregnancy body mass index and gestational weight gain with cardio‐metabolic risk factors in adolescent offspring: a prospective cohort study. (3rd November 2015) - Gaillard, R; Welten, M; Oddy, WH; Beilin, LJ; Mori, TA; Jaddoe, VWV; Huang, R‐C
Abstract : Objective: To assess the associations of maternal prepregnancy body mass index (BMI) and rates of early‐pregnancy, mid‐pregnancy and total gestational weight gain with adolescent body fat distribution and cardio‐metabolic outcomes. Design: Population‐based prospective cohort study. Setting: Western Australia. Population: Thousand three hundred and ninety‐two mothers and their children. Methods: Maternal prepregnancy weight was assessed by questionnaire. Maternal weights at a mean of 16.5 ± 2.2 SD and 34.1 ± 1.5 SD weeks of gestation were obtained from medical records. Offspring adiposity and cardio‐metabolic outcomes were assessed at a median age 17.0 years [95% confidence interval (CI) range: 16.7, 17.7]. Main outcome measures: Adolescent BMI, waist circumference (WC), waist‐to‐hip ratio (WHR), blood pressure, total and HDL‐cholesterol, triglycerides, insulin, glucose and HOMA‐IR. Results: Higher prepregnancy BMI was associated with higher adolescent BMI, WC, WHR, systolic blood pressure, insulin, glucose and HOMA‐IR levels ( P ‐values <0.05). Adjustment for adolescent current BMI attenuated the associations of prepregnancy BMI with adolescent cardio‐metabolic outcomes. Higher weight gain in early‐pregnancy, but not mid‐pregnancy, was associated with higher adolescent BMI, WC and WHR ( P ‐values <0.05), but not with other cardio‐metabolic risk factors. Total gestational weight gain was associated with adolescent BMI and WC ( P ‐values <0.05). Higher prepregnancy BMI and early‐pregnancy weight gain were associated with increased risks of the high‐metabolic risk cluster in adolescents (OR 1.57, 95% CI 1.33, 1.85 and OR 1.23, 95% CI 1.03, 1.47 per SD increase in prepregnancy BMI and early‐pregnancy weight gain, respectively). Conclusions: Higher maternal prepregnancy BMI and early‐pregnancy weight gain rate are associated with an adverse adolescent cardio‐metabolic profile. These associations are largely mediated by adolescent BMI. Tweetable abstract: Prepregnancy BMI and early‐pregnancy WG rate are associated with adverse adolescent cardio‐metabolic profile. Tweetable abstract: Prepregnancy BMI and early‐pregnancy WG rate are associated with adverse adolescent cardio‐metabolic profile.